2023
DOI: 10.1101/2023.03.02.529724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Tumor Explants Elucidate a Cascade of Paracrine SHH, WNT, and VEGF Signals Driving Pancreatic Cancer Angiosuppression”

Abstract: The sparse vascularity of Pancreatic Ductal Adenocarcinoma (PDAC) presents a mystery: what prevents this aggressive malignancy from undergoing neoangiogenesis to counteract hypoxia and better support growth? An incidental finding from prior work on paracrine communication between malignant PDAC cells and fibroblasts revealed that inhibition of the Hedgehog (HH) pathway partially relieved angiosuppression, increasing tumor vascularity through unknown mechanisms. Initial efforts to study this phenotype were hind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Lysates from 4 of the 9 toxin-producing strains (Supp Fig 1A) were effective at reducing the viability of nearly all PDAC lines examined: Theta toxin, Magainin, Heat Stable Enterotoxin (HSEnt), and Hemolysin E (HlyE) (Fig 1A). To more effectively model toxin effects on intact tumor tissue, we carried out a secondary screen using PDAC explant cultures derived from pancreatic tumors in KPC mice ( 3, 17 ). Of the four candidate strains tested, Theta toxin stood out for its ability to induce apoptosis, as measured by cleaved caspase 3 (CC3) staining, compared to a GFP-expressing control strain (Fig 1B, Supp Fig 1B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lysates from 4 of the 9 toxin-producing strains (Supp Fig 1A) were effective at reducing the viability of nearly all PDAC lines examined: Theta toxin, Magainin, Heat Stable Enterotoxin (HSEnt), and Hemolysin E (HlyE) (Fig 1A). To more effectively model toxin effects on intact tumor tissue, we carried out a secondary screen using PDAC explant cultures derived from pancreatic tumors in KPC mice ( 3, 17 ). Of the four candidate strains tested, Theta toxin stood out for its ability to induce apoptosis, as measured by cleaved caspase 3 (CC3) staining, compared to a GFP-expressing control strain (Fig 1B, Supp Fig 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Murine tumors were collected following humane euthanasia and trimmed of healthy pancreas tissue in a sterile petri dish. Tissues were processed into explant slices and cultured as previously described ( 3, 17 ). Explants were treated with murine explant media supplemented with 10% bacterial toxin lysate, replaced daily for up to 3 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Explant culture sponges and optimized culture media were prepared as previously described in Hasselluhn and Decker-Farrell et al 26 . Human tissue samples were obtained from de-identified patients undergoing resection surgeries, primarily pancreaticoduodenectomy (Whipple) or distal pancreatectomy, at New York-Presbyterian/Columbia University Irving Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have demonstrated that various stromal cells resident in PDAC tissues can modulate the sensitivity of malignant cells to therapy 25 . To assess the potency of RMC-7977 in the context of an intact, all-human microenvironment, we employed an ex vivo human PDAC explant model 26 , comprising cultured intact slices of freshly resected human PDAC tissue from patients at New York Presbyterian Hospital/Columbia University Irving Medical Center. Immunohistochemistry performed on PDAC explants treated for 24 hours with RMC-7977 showed a concentration-dependent decrease in pERK expression with an accompanying increase in the apoptosis marker, cleaved caspase 3 (CC3), with maximal changes at 100 nM, the highest concentration tested (Fig.…”
Section: Rmc-7977 Exhibits Broad Anti-cancer Activity In Pdac Modelsmentioning
confidence: 99%